Infants Perceive Three-Dimensional Subjective Contours. (December 2018) - Kavšek, Michael; Braun, Stephanie
The addition of crossed horizontal disparity enhances the clarity of illusory contours compared to pictorial illusory contours and illusory contours with uncrossed horizontal disparity. Two infant-controlled habituation–dishabituation experiments explored the presence of this effect in infants 5 months of age. Experiment 1 examined whether infants are able to distinguish between a Kanizsa figure with crossed horizontal disparity and a Kanizsa figure with uncrossed horizontal disparity. Experiment 2 tested infants for their ability to differentiate between a Kanizsa figure with crossed horizontal disparity and a two-dimensional Kanizsa figure. The results provided evidence that the participants perceived the two- and the three-dimensional illusory Kanizsa contour, the illusory effect in which was strengthened by the addition of crossed horizontal disparity.